2019
DOI: 10.1136/bmjopen-2018-027101
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and non-clinical variables associated with preventive and curative dental service utilisation: a cross-sectional study among adolescents and young adults in Central Mexico

Abstract: ObjectiveThe present study aimed to identify preventive and curative dental health service utilisation (DHSU) in the context of associated clinical and non-clinical factors among adolescents and young adults in Mexico.DesignCross-sectional study.SettingApplicants to a public university in Mexico.ParticipantsParticipants were 638 adolescents and young adults aged 16–25 randomly selected from university applicants.InterventionsData were collected using a self-administered questionnaire filled out by the students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
0
9
0
2
Order By: Relevance
“…Mexico is a middle-income country where the majority of the population, especially children and adolescents, have limited access to preventive and curative dental health services. 17,29 This happens against an epidemiological landscape where caries prevalence is high and many lesions are not treated. 5 Results of the present study revealed a positive association between the reason for appointment (curative / emergency) and dental pain as factors more strongly associated with previous pain.…”
Section: Discussionmentioning
confidence: 99%
“…Mexico is a middle-income country where the majority of the population, especially children and adolescents, have limited access to preventive and curative dental health services. 17,29 This happens against an epidemiological landscape where caries prevalence is high and many lesions are not treated. 5 Results of the present study revealed a positive association between the reason for appointment (curative / emergency) and dental pain as factors more strongly associated with previous pain.…”
Section: Discussionmentioning
confidence: 99%
“…A largely unregulated system, under the control of dental professionals, leaves costs subject to shifts in the dental marketplace. Finally, many public and private universities across the country have dental clinics that offer services to the general population at prices far below those of private practice [6,38,41,42].…”
Section: Context Of Dental Services In Mexicomentioning
confidence: 99%
“…A national health survey in 2018 estimated that 96% of Indonesians did not visit a dentist within the past year [ 1 ]. Several factors that influence dental service utilisation have been identified in other countries, such as age, gender, marital status, residential area, education, income, health insurance and individual health needs, including dental pain and self-perceived oral health [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%